Authentic Sociology Learning Design: A Social Constructivism Approach Through Collaboration with Government Social Programs - Budiati, Atik Catur; Indria Liestyasari, Siany Indria; Narendra Parahita, Bagas; Syafutra Siregar, Riadi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: Studying sociology gains real significance when it is linked to real-life situations, creating a challenge for teachers to incorporate society into their sociology lessons. This study seeks to connect sociological content with social programs through collaborative projects. Social programs run by both the public and private sectors can provide an individual with a genuine understanding of social issues. Method: The study employs a qualitative design with a social constructivist approach, emphasizing collaborative learning through interaction, discussion, and sharing of knowledge among students. Data were gathered through interviews and document analysis. The informants consist of sociology teachers, sociology researchers, and coordinators of sociology education programs. Additionally, the study involves informants from organizations responsible for implementing social programs. To integrate sociological material, it is necessary to simplify sociological material to facilitate the process of collaboration, bringing society into sociology classes. Results: The integration of government social programs into high school sociology instruction through a social constructivist approach fosters meaningful, contextual, and in-depth learning. By engaging in real-life experiences, participating in social dialogue, and receiving mentorship from teachers and peers, students not only grasp sociological concepts on a theoretical level but also cultivate empathy, social awareness, and essential 21st-century skills. Novelty: This study emphasizes on integrating government social programs as contextual learning resources through intersectoral collaboration. This approach positions these programs as authentic learning environments enabling students to connect sociological theories with real social conditions, aligning with Vygotsky’s social constructivism and supporting deeper conceptual understanding in sociology learning.